Efektivitas Pembelajaran Berbasis AI Gemini untuk Meningkatkan Keterampilan Fotografi di SMKN 3 Kuningan - Maulana, Aldy; Fazrin N, Sofhian (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to measure the effectiveness of AI Gemini-based learning in improving the photography skills of students at SMKNegeri 3 Kuningan. The research method used was a quantitative approach with a One Group Pretest-Posttest Design. The sample consisted of 36 students of grade X DKV selected using purposive sampling technique. Data were collected through pretest, posttest, questionnaires, and observations, and analyzed using SPSS version 27. The results showed that the average pretest score of 25.75 increased to 33.75 in the posttest, with a mean difference of 8 points. The Paired Sample t-Test indicated a significant difference before and after the treatment (t = −60.083; p = 0.000 < 0.05). Correlation analysis revealed a very strong relationship between the effectiveness of AI Gemini and photography skills (r = 0.937; p = 0.000). Furthermore, simple linear regression analysis produced the equation Y = 5.767 + 1.021X with a coefficient of determination R² = 0.878, meaning that AI Geminibased learning contributes 87.8% to students’ photography skills. Therefore, it can be concluded that the implementation of AI Gemini-based learning is effective in enhancing students’ photography skills, particularly in understanding the exposure triangle, image composition, and lighting techniques.